A comparative perspective on the evolution of Romance clausal structure - Wolfe, S (John Benjamins Publishing, 2016)
The article presents a comparative analysis of the diachronic evolution of Romance clausal structure from Classical Latin through to the late medieval period, with particular reference to the Verb Second (V2) property. In the medieval period three distinct diachronic stages can be identified as regards V2: a C-VSO stage attested in Old Sardinian, a 'relaxed' V2 stage across Early Medieval Romance and maintained into 13th and 14th century Occitan and Sicilian, and a 'strict' V2 stage attested in 13th and 14th century French, Spanish and Venetian. The C-VSO grammar found in Old Sardinian is a retention of the syntactic system attested in late Latin textual records, itself an innovation on an 'incipient V2' stage found in Classical Latin, where V-to-C movement and XPfronting receive a pragmatically or syntactically marked interpretation.